PENGARUH POLA ASUH ORANGTUA TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Amir Pada (Universitas Negeri Makassar, 2021)
This study aims to see the effect of authoritarian, permissive and democratic parenting partially on the learning outcomes of fourth grade students of SD Inpres Sero, Kabupaten Gowa and to see the effect of authoritarian parenting, permissiveness and democratization simultaneously on learning outcomes of fourth grade students of SD Inpres Sero, Kabupaten Gowa. The results showed that parenting contributed 11.6% to learning outcomes, permissive parenting contributed 20.5% to learning outcomes and democratic parenting contributed 16.1% to learning outcomes. Meanwhile, authoritarian, permissive and domocratic parenting patterns simultaneously affect student learning outcomes. The big influence is 19.6% and the rest are other variables not selected in this study